Public Debt and r - g at Risk - Lian, Weicheng (IMF Working Papers; Working Paper ;, 2020)
As interest rate-growth differentials (r-g) turned negative in many countries, governments consider pursuing fiscal expansion and the potential risks involved. Using a large sample of advanced and emerging economies, our analysis suggests that high public debts can lead to adverse future r-g dynamics. Specifically, countries with higher initial public debt experience (i) a shorter duration of negative r-g episodes and a higher probability of reversal, (ii) higher average r-g, and (iii) a more right-skewed r-g distribution, that implies higher down-side risks. Furthermore, high-debt countries experience larger increases in interest rates in response to (iv) an unexpected decline in domestic output and (v) an increase of global volatility. Results are stronger when public debts are denominated in foreign currencies.